Chemical composition of Essential oil from Lindera rufa Hook. f. a New Natural Source of Camphor - Thang, Tran Dinh; Dai, Do Ngoc; Dung, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 27 No 4, 2011)
Abstract. The chemical composition of the leaf oil obtained by hydrodistillation of Lindera rufa Hook. f. were study by GC, GC/MS Thirty-tow compounds were identified representing 99.65% of the oil with camphor (67.46%) as major constituent. Other thirty-two components were found with lower content. The oil yield was 0.91% on fresh leaves. Keywords: Lindera rufa, Lauraceae, essential oil composition, camphor.